Let-7g* and miR-98 Reduce Stroke-Induced Production of Proinflammatory Cytokines in Mouse Brain - Bernstein, David L.; Rom, Slava (Frontiers in Cell and Developmental Biology, 2020)
Stroke is a debilitating illness facing healthcare today, affecting over 800,000 people and causing over 140,000 deaths each year in the USA. Despite being the third-leading cause of death, very few treatments currently exist for stroke. Often, during an ischemic attack, the blood-brain barrier (BBB) is significantly damaged, which can lead to altered interactions with the immune system, and greatly worsen the damage from a stroke. The impaired, BBB promotes the infiltration of peripheral inflammatory cells into the brain, secreting deleterious mediators (cytokines/chemokines) and resulting in permanent barrier injury. let-7 microRNAs (miRs) are critical for regulating immune responses within the BBB, particularly after ischemic stroke. We have previously shown how transient stroke decreases expression of multiple let-7 miRs, and that restoration of expression confers significant neuroprotection, reduction in brain infiltration by neutrophils, monocytes and T cells. However, the specific mechanisms of action of let-7 miRs remain unexplored, though emerging evidence implicates a range of impacts on cytokines. In the current study, we evaluate the impacts of miR-98 and let-7g* on targeting of cytokine mRNAs, cytokine release following ischemic stroke, and cell-specific changes to the neurovascular space. We determined that miR-98 specifically targets IP-10, while let-7g* specifically aims IL-8, and attenuates their levels. Both produce strong impacts on CCL2 and CCL5. Further, let-7g* strongly improves neurovascular perfusion following ischemic stroke. Together, the results of the study indicate that let-7 miRs are critical for mediating endothelial-immune reactions and improving recovery following ischemic stroke.